Analogical modeling : an exemplar-based approach to language - Skousen, Royal; Lonsdale, Deryle; Parkinson, Dilworth B., 1951- (Human cognitive processing, 2002)
Analogical Modeling (AM) is an exemplar-based general theory of description that uses both neighbors and non-neighbors (under certain well-defined conditions of homogeneity) to predict language behavior. This book provides a basic introduction to AM, compares the theory with nearest-neighbor approaches, and discusses the most recent advances in the theory, including psycholinguistic evidence, applications to specific languages, the problem of categorization, and how AM relates to alternative approaches of language description (such as instance families, neural nets, connectionism, and optimali.